1993
DOI: 10.1152/ajpregu.1993.265.3.r568
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-derived relaxing factor responses in Doca-salt hypertensive rats

Abstract: This study examined the contribution of endothelium-derived relaxing factor (EDRF) to the susceptibility of uninephrectomized rats to deoxycorticosterone acetate (DOCA)-salt hypertension. N omega-nitro-L-arginine, a probe for EDRF, produced smaller increases (P < 0.001) in mean arterial pressures in anesthetized hypertensive DOCA-salt rats than in sham rats. Acute L-arginine administration (300 mg/kg body wt i.v.) failed to reduce pressure in anesthetized DOCA-salt rats. Chronic oral and intraperitoneal L-argi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…They concluded that the increased NO release resulted from a reduction in high blood pressure. Reduced release of endothelium-derived relaxing factor (NO) in the aorta has been demonstrated in DOCA hypertensive rats (37) . However, the reduction in MCVR in our study may not have been caused the increase in NO release, because we found no reduction in high blood pressure in DOCA hypertensive rats treated with candesartan cilexetil.…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that the increased NO release resulted from a reduction in high blood pressure. Reduced release of endothelium-derived relaxing factor (NO) in the aorta has been demonstrated in DOCA hypertensive rats (37) . However, the reduction in MCVR in our study may not have been caused the increase in NO release, because we found no reduction in high blood pressure in DOCA hypertensive rats treated with candesartan cilexetil.…”
Section: Resultsmentioning
confidence: 99%
“…Basal production of NO and endothelium-dependent relaxation are attenuated in conduit arteries of deoxycorticosterone acetate (DOCA)-salt hypertensive rats. [5][6][7] However, the role of NO in regulating basal tone in small arteries of DOCA-salt rats has not been resolved. [7][8][9] Oxidative stress contributes to the pathogenesis of hypertension.…”
mentioning
confidence: 99%
“…2) Recent studies reported that the synthesis or release of endothelium-derived relaxing factor (EDRF) and responses to EDRF are impaired in this model of hypertension. 3,4) In addition, we found the hypotensive effect of FR 139317 or ABT-627, both of which are selective endothelin ET A receptor antagonists , in DOCAsalt hypertensive rats, thereby suggesting that endothelin and ET A receptors are closely involved in the maintenance of DOCA-salt hypertension. 5,6) The mechanisms by which BEC prevents the development of DOCA-salt hypertension are unclear, but feeding with BEC for 5 weeks may affect the activities of the above neural and/or humoral factors.…”
Section: Discussionmentioning
confidence: 63%